2010
DOI: 10.1111/j.1365-2486.2009.02104.x
|View full text |Cite
|
Sign up to set email alerts
|

Variability in exchange of CO2 across 12 northern peatland and tundra sites

Abstract: Many wetland ecosystems such as peatlands and wet tundra hold large amounts of organic carbon (C) in their soils, and are thus important in the terrestrial C cycle. We have synthesized data on the carbon dioxide (CO 2 ) exchange obtained from eddy covariance measurements from 12 wetland sites, covering 1-7 years at each site, across Europe and North America, ranging from ombrotrophic and minerotrophic peatlands to wet tundra ecosystems, spanning temperate to arctic climate zones. The average summertime net eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
241
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 250 publications
(261 citation statements)
references
References 70 publications
17
241
3
Order By: Relevance
“…In particular, climate warming can directly affect C fluxes from peatlands. Ecosystem respiration has been found to increase in response to a 1 • C soil warming in a subarctic bog (Dorrepaal et al, 2009) and to vary depending on seasonal temperature patterns (Lund et al, 2010). Methane emissions are also strongly dependent on soil temperature (Treat et al, 2007;Kettridge and Baird, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, climate warming can directly affect C fluxes from peatlands. Ecosystem respiration has been found to increase in response to a 1 • C soil warming in a subarctic bog (Dorrepaal et al, 2009) and to vary depending on seasonal temperature patterns (Lund et al, 2010). Methane emissions are also strongly dependent on soil temperature (Treat et al, 2007;Kettridge and Baird, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Warm and dry conditions in peatlands can promote CO 2 uptake by enhancing GPP, diminish uptake by limiting moisture (Roulet et al, 2007;Charman et al, 2013) or accelerate CO 2 release by enhancing R (Hanson et al, 2000;Davidson and Janssens, 2006;Lund et al, 2010;Ise et al, 2008;Cai et al, 2010). In a dwarf-shrub pine bog, Pihlatie et al (2010) found that the CO 2 flux peak followed the increase in air and soil temperature closely, being higher (uptake) on warm and lower (emission) on cold days.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the tundra may have acclimated to temperature changes, and has once again turned back to a sink after acting as a source in the 1980s (Oechel et al 2000). Since climatic factors may vary widely from year to year, there is also a large degree of interannual variability in tundra NEE, gross primary productivity (GPP), and ecosystem respiration (ER) (Kwon et al 2006, Lafleur and Humphreys 2008, Lund et al 2010.…”
Section: Introductionmentioning
confidence: 99%